THE RELATIONSHIP OF TOTAL CIGARETTE CONSUMPTION AND PEAK EXPIRATORY FLOW RATE VALUES ON YOUNG ADULT MEN - Sukreni, Ni Putu Suci; Wibawa, Ari; Dinata, I Made Krisna (Majalah Ilmiah Fisioterapi Indonesia; Vol 5 No 3 (2017): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2017.v05.i03.p12, 2018)
ABSTRACT Smoking can affect health, especially lung health. This study aims to find the relationship of total cigarette consumption and peak expiratory flow rate values. Using cross-sectional analytical design conducted in 2017 in March on Udayana University Faculty of Engineering students aged 20-24 years with sampling method consecutive sampling obtained 91 respondents. Measurement of the Total Cigarette Smoking Quantity was done using a questionnaire that refers to the smoking habit and Peak Flow Meter to assess the Peak Flow of Expiration. Data was analyzed by Spearman's Rho correlation coefficient test showed that p = 0,038 (p <0,05) with r = -0,218. In conclusion there is a significant relationship but the strength is weak and negative or not unidirectional between total cigarette consumption and peak expiratory flow rate on young adult men. The total of cigarettes consumption per day amounted to 10.69 stems. While the average peak expiratory flow rate value amounted to 405.16 L / min. Keywords : Total Cigarette Consumption, Peak Expiratory Flow Rate Values, Young Adult Men